Joint line rim-plate combined with horizontal belt plate in the treatment of hyperextension tibial plateau fracture: our clinical and radiological results - Gu, Yanqing; Ma, Cheng; Zhao, Lei; Jiang, Chunzhi (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the efficacy of combined medial and lateral approaches with horizontal belt plate fixation for treating hyperextension-type bicondylar tibial plateau fractures.MethodsA retrospective analysis was conducted on 10 patients with hyperextension-type bicondylar tibial plateau fractures treated between March 2023 and March 2024 using a combined medial-lateral approach and anterior joint line rim-plate fixation. During surgery, the infrapatellar tendon was released to create a horizontal rim-plate channel. A pre-contoured tubular locking plate was fixed anteriorly to the tibial plateau. A T-shaped main plate was placed on the medial or lateral side based on fracture patterns. Screws from medial, lateral, and anterior plates formed a “fence-like” structure.ResultsAll 10 patients achieved bony union with an average follow-up of 14 months. Postoperative radiographs demonstrated restored posterior tibial slope angles. The average Hospital for Special Surgery (HSS) knee score was 88.7, with knee range of motion averaging 113°. No wound complications or implant failures were observed.ConclusionPreliminary results indicate that combined medial-lateral approaches with horizontal belt plate fixation are a safe and effective option for hyperextension-type bicondylar tibial plateau fractures. Restoration of lower limb alignment, correction of posterior tibial slope, and joint surface congruity are critical for optimal outcomes.